Republikanie i demokraci wobec procesu judykalizacji amerykańskiej polityki. Analiza z perspektywy problemu legalizacji małżeństw osób tej samej płci - Laidler, Paweł (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Republicans and Democrats on the process of judicalization of American politics. Analysis from the perspective of legalization of same‑sex marriages In June 2015 the Supreme Court issued a decision legalizing same‑sex marriages in the United States. The problem of LGBT rights has become one of the major ideological clashes between the Republicans and Democrats, who present opposite approaches towards the scope of the constitutional right to privacy. The Obergefell v. Hogdes precedent raises again the question of judicialization of American politics, the process which can be observed since the 1950s, and which becomes an apparent result of American courts’ impact on important social and political relations. The article analyzes the arguments raised in political discussion over the issue of judicialization of politics from the perspective of the evolution of LGBT rights in the United States. Key words: legalization of same‑sex marriages, LGBT rights, American courts’ impact, judicalization of American politics